The sequence of acquisition of personal pronoun case and person reference among 6 year old children in two selected Malaysian kindergartens - Samad, Arshad Abd; Arshad, Nurul Iman (Australian International Academic Centre, 2017)
Pronoun case and person reference refer to the position of the pronoun in the sentence and the person the pronoun refers to respectively. Examining the acquisition of pronoun case and person reference among young children can be insightful as, besides their obvious relevance to language development, both these constructs can have implications on other aspects of child development. Attention given by children to these various constructs may indicate the importance children place on the concept of ego and self as well as on social relations. The sequence of acquisition of personal pronouns among these children is therefore an important phenomenon to be examined as it can reflect linguistic and socio-cognitive development. This largely descriptive study examines the sequence of acquisition of the English pronouns among forty 6 year old Malaysian children learning ESL in two kindergartens. The children in the study were presented with 33 drawings to assess their familiarity with case and person reference expressed through English personal pronouns. They were required to select the correct pronoun from three pronouns that were used to describe each drawing. This paper reports on the accuracy rates for each pronoun and assumes that high accuracy rates indicate a more complete acquisition of the pronoun. Error forms by the children were also be identified and examined. Data obtained were compared to acquisition sequences in the literature and general implications related to the acquisition of personal pronouns among children in an ESL setting in Malaysia will be discussed.